2016
DOI: 10.4103/0366-6999.178959
|View full text |Cite
|
Sign up to set email alerts
|

Initiating Characteristics of Early-onset Type 2 Diabetes Mellitus in Chinese Patients

Abstract: Background:Type 2 diabetes mellitus (T2DM) has traditionally been considered to affect mainly the elderly; however, the age at diagnosis has gradually reduced in recent years. Although the incidence of young-onset T2DM is increasing, it is still not fully clear the onset characteristics and risk factors of early-onset T2DM. The aim of this study was to describe the initiating characteristics of early-onset T2DM in Chinese patients and evaluate the risk factors for diabetes mellitus.Methods:This cross-sectional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 29 publications
2
15
0
1
Order By: Relevance
“…Although healthcare workers in China’s top-three hospitals treat numerous patients, few workers are mindful of their own health issues. Studies have shown that continuous exposure to factors such as lack of sleep, exercise and a regular diet, as was found here, may increase the risk of chronic diseases among healthcare workers 10 62 63. The fact that healthcare workers do not pay proper attention to their own health should be recognised by the government and society.…”
Section: Resultsmentioning
confidence: 57%
“…Although healthcare workers in China’s top-three hospitals treat numerous patients, few workers are mindful of their own health issues. Studies have shown that continuous exposure to factors such as lack of sleep, exercise and a regular diet, as was found here, may increase the risk of chronic diseases among healthcare workers 10 62 63. The fact that healthcare workers do not pay proper attention to their own health should be recognised by the government and society.…”
Section: Resultsmentioning
confidence: 57%
“…These data suggest that adults with early onset T2DM represent a substantial proportion of patients consuming medical resource even in economically underdeveloped areas of China. Of note, patients with early onset T2DM, despite of younger ages and shorter durations of diabetes, had poorer plasma glucose control than those patients with late onset [ 8 , 15 , 16 ]. Thus, prevention of diabetes, especially among individuals aged below 40 years, should be regarded as a public health emergency in such area.…”
Section: Discussionmentioning
confidence: 99%
“…[ 24 ] Moreover, they often had dyslipidemia and systemic prothrombotic state related to the activation of the platelet aggregation and coagulation systems. [ 6 25 ] Altogether, these made diabetic patients a challenging subpopulation who should be given more specific treatment and management. Thus, it was very significant to find reliable factors to predict the risk of ISR, especially in diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…A recent multicenter study showed that the prevalence of dyslipidemia had reached up to 67.1% in diabetic patients in China,[ 6 ] which was uniquely manifested by the high level of VLDL-C and TG, low level of HDL-C, but the usually normal level of LDL-C.[ 7 ] Increasing evidence indicated that triglycerides-rich lipoprotein (TGRL) was one of the most important residual risk factors of CVD beyond LDL-C.[ 10 26 27 ] The fasting serum TG was usually measured as the most common biomarker of TGRL. However, many prospective epidemiological studies suggested that serum TG might not capture the true extent of CVD risk, and failed to fully reflect the cholesterol content of VLDL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation